2007
DOI: 10.2109/jcersj.115.374
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Etched Sharpened Tip of Transparent Crystallized Glass Fibers with Nonlinear Optical Ba2TiSi2O8 Nanocrystals

Abstract: Glass fibers with a diameter of Ĭ100 mm are drawn by just pulling up melts of 40BaOெ20TiO 2 ெ40SiO 2 glass, and transparent crystallized glass fibers consisting of nonlinear optical fresnoite Ba 2 TiSi 2 O 8 nanocrystals particle size: Ĭ100-200 nm are fabricated by crystallization of glass fibers. Precursor glass fibers and nanocrystallized glass fibers are etched chemically using a meniscus method, in which an etching solution of 0.1 wt!-HFhexane is used. Glass fibers with sharpened tips e.g., the taper lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The results shown in Figures 1 and 2 propose that at least, at the laser irradiation condition of P = 0.8 W and S = 4 μm/s, only the crystal growth of β-BBO is taking place during the laser scanning in 8Sm2O3-42BaO-50B2O3 glass without causing any nucleation, and this would be one of the key points for the laser patterning of β-BBO crystals with high orientation. It should be pointed out that highly oriented Ba2TiSi2O8 crystal lines have been patterned by laser irradiation in 40BaO-20TiO2-40SiO2 glass, although Ba2TiSi2O8 nanocrystals are formed by heat treatment in an electric furnace (Enomoto et al, 2007;Honma et al, 2008a,b;Maruyama et al, 2008). Similar behaviors have been observed in the laser patterning and nano-scaled crystallization of the formation of nonlinear optical BaAlBO3F2 crystals in 50BaF2-25Al2O3-25B2O3 glass (Shinozaki et al, 2012).…”
Section: /μMsupporting
confidence: 52%
“…The results shown in Figures 1 and 2 propose that at least, at the laser irradiation condition of P = 0.8 W and S = 4 μm/s, only the crystal growth of β-BBO is taking place during the laser scanning in 8Sm2O3-42BaO-50B2O3 glass without causing any nucleation, and this would be one of the key points for the laser patterning of β-BBO crystals with high orientation. It should be pointed out that highly oriented Ba2TiSi2O8 crystal lines have been patterned by laser irradiation in 40BaO-20TiO2-40SiO2 glass, although Ba2TiSi2O8 nanocrystals are formed by heat treatment in an electric furnace (Enomoto et al, 2007;Honma et al, 2008a,b;Maruyama et al, 2008). Similar behaviors have been observed in the laser patterning and nano-scaled crystallization of the formation of nonlinear optical BaAlBO3F2 crystals in 50BaF2-25Al2O3-25B2O3 glass (Shinozaki et al, 2012).…”
Section: /μMsupporting
confidence: 52%
“…The glass plates with polished surfaces were heat-treated at temperatures of 750, 760, 770, 780, and 790°C for 1 h in air and cooled to room temperature at a cooling rate of 1 K/min in an electric furnace. As demonstrated in the previous papers [8][9][10][11][12][13][14], the glass of 40BaO-20TiO 2 -40SiO 2 (mol%) shows the crystallization of fresnoite Ba 2 TiSi 2 O 8 nanocrystals (i.e., BTS nanocrystals) with diameters of 100 nm through a homogeneous nucleation. The XRD patterns at room temperature for some heat-treated samples prepared in this study are shown in Fig.…”
Section: Morphology and Dispersion State Of Ba 2 Tisi 2 O 8 Nanocrystalsmentioning
confidence: 56%
“…Although there have been many reports on the glass-ceramics containing BTS nanocrystals [5][6][7][8][9][10][11][12][13][14], information on the morphology and dispersion state of BTS nanocrystals is limited [20] heat-treated at 760°C for 1 h indicate the early stage of crystallization of fresnoite Ba 2 TiSi 2 O 8 in the glass of 40BaO-20TiO 2 -40SiO 2 . That is, even in the glass with the composition corresponding to the fresnoite Ba 2 TiSi 2 O 8 crystalline phase, not only bulk crystallization but also surface crystallization is taking place at the same time.…”
Section: Morphology Of Ba 2 Tisi 2 O 8 Nanocrystalsmentioning
confidence: 99%
See 2 more Smart Citations